The Palestinian Triangle between Judaization and Annexation (1949-2020) - Djeber chamali, Ilham (Milev Journal of Research and Studies, 2021)
The subject of the study revolves around the Israeli concerns about the danger of the Arab demographic expansion on the future of the Jewishness of the state and the most important Israeli attitudesand projects towards the Palestinian Triangle from 1949 until 2020. The study is divided into three axes, preceded by an introduction, followed by a conclusion. The first axis dealt with the stages of theannexing process of the Triangle since (1948) in search of the newly established entity of Israel about a strategic depth by controlling the largest possible area of land with a security and strategic dimension. This axis also examines the Israeli motives behind the idea of abandoning the Triangle in favor of the Palestinian Authority. The second axis monitors Judaization projects in detail, in addition to shedding light on annexation projects, population exchange. Finally, the third axis discussed the role of the Israeli Studies Centers in Israeli decision-making, especially towards the process of annexing the Triangle to the Palestinian Authority, in addition to the factors affecting the decision to exchange lands and annexation between security and demographic justifications